The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1063/1.4734395
|View full text |Cite
|
Sign up to set email alerts
|

Matrix role in Ge nanoclusters embedded in Si3N4 or SiO2

Abstract: Ge nanoclusters (NCs), synthesized by ion implantation and annealing up to 900 °C, result small (∼2 nm) and amorphous in Si3N4, crystalline and much larger in SiO2. The NCs ripening and crystallization kinetics in Si3N4 is retarded by larger interfacial energy and lower diffusivity of Ge in comparison to SiO2. Ge NCs absorb light more efficiently when embedded in Si3N4 than in SiO2. A significant effect of the barrier height on absorption was evidenced, in agreement with effective mass theory predictions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…This point is further confirmed by previous observation of stoichiometric Si 3 N 4 and SiO 2 matrices implanted with Ge. 18 In that case, the lower diffusivity of Ge in Si 3 N 4 (below 7 Â 10 À17 cm 2 /s at 850 C) compared with SiO 2 (of the order of 10 À13 cm 2 /s at 800 C 28 ) retarded the QD ripening in Si 3 N 4 and led to the formation of a narrow size distribution ($2 nm) of Ge QDs in Si 3 N 4 against a more sparse array of larger QDs (size $ 3 _ 24 nm) in SiO 2 . In this paper, a similar behavior occurs for PECVD SiGeO and SiGeN alloys, indicating a clear role of the embedding matrix in the nucleation and growth of Ge QDs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This point is further confirmed by previous observation of stoichiometric Si 3 N 4 and SiO 2 matrices implanted with Ge. 18 In that case, the lower diffusivity of Ge in Si 3 N 4 (below 7 Â 10 À17 cm 2 /s at 850 C) compared with SiO 2 (of the order of 10 À13 cm 2 /s at 800 C 28 ) retarded the QD ripening in Si 3 N 4 and led to the formation of a narrow size distribution ($2 nm) of Ge QDs in Si 3 N 4 against a more sparse array of larger QDs (size $ 3 _ 24 nm) in SiO 2 . In this paper, a similar behavior occurs for PECVD SiGeO and SiGeN alloys, indicating a clear role of the embedding matrix in the nucleation and growth of Ge QDs.…”
Section: Resultsmentioning
confidence: 99%
“…19 However, contrasting results appear in the literature for the growth kinetics of QDs in SiO 2 20 On the contrary, stoichiometric Si 3 N 4 films implanted with Ge showed retarded QD ripening and crystallization kinetics with respect to Ge QDs in SiO 2 implanted with the same Ge dose. 18 A significant role of the embedding matrix was also found for the optical bandgap of these systems, with Ge QDs in Si 3 N 4 absorbing light more efficiently than in SiO 2 . 18 This effect, together with the lower tunneling barrier height offered by Si 3 N 4 , could potentially open a route toward the fabrication of efficient photodetectors and solar cells.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Several studies demonstrated how the optical properties of Si nanostructures can be varied by solely managing the nanostructure shape, 15 the QD crystalline structure, 16,17 or the potential barriers surrounding the QD. [18][19][20] Even though a multilayerednanostructure approach and an appropriate surface passivation could allow an efficient control of QCE via size-tuning only, 13 the optical properties of confined systems can be † SC contributed to sample processing, characterization, data analysis and interpretation, and drafted the manuscript. AMM performed STEM and EELS analysis, together with data interpretation.…”
Section: Introductionmentioning
confidence: 99%